The relation of commerce to civilization - Frowe, Eugene Leonard (My University, 1894)
Introduction: Commerce is the interchange of services or products between persons of different industrial functions, effected either directly or through the intervention of a third party. It is coerced with the dawn of civilization. When people cease to supply themselves with the various articles and accommodations that are necessary to their welfare as well as the luxuries of life; and when they commence to use articles not native of their own section of country then commercial intercourse is established. The chief principles and results of commerce are as follows. 1. The division of labor among the inhabitants of the same place is established. 2. Then between neighboring places. 3. And finally between the countries of the world. Commerce originated with man while in the barbaric state. The man hunted, fished and warred- he obtained food for the family while on his expeditions. The wife did the cooling, planted, tended and harvested the corn and then transformed it into an edible state.
Citation: Frowe, Eugene Leonard. The relation of commerce to civilization. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Commerce; Civilization; Agriculture; Economics; Theses; Manuscripts (documents)